2023
DOI: 10.3390/app13105859
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Analysis of the Nonlinear Dynamics of Shimmed Conical Gas Foil Bearings

Abstract: Conical gas foil bearings (CGFBs) have the potential to halve the number of necessary bearings in a conventional rotor system supported by gas foil bearings. Transient simulations of gas foil journal bearings and gas foil thrust bearings have proven their necessity to accurately predict the safe operating range of such bearings. This work presents the first transient model able to simulate the three-dimensional dynamics of CGFBs. The static behaviour of a single CGFB with a uniform bearing clearance is compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…As the dynamic viscosity coefficient of air is low, the air foil bearing provides limited damping under high-speed conditions and may suffer from hydrodynamic instability; thus, dynamic design and analysis are necessary for the safe operation of a rotor. Obtaining the dynamic characteristics of a bearing is a prerequisite for rotor dynamic design [5,6]. The dynamic coefficient of a bearing is typically used to describe the dynamic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…As the dynamic viscosity coefficient of air is low, the air foil bearing provides limited damping under high-speed conditions and may suffer from hydrodynamic instability; thus, dynamic design and analysis are necessary for the safe operation of a rotor. Obtaining the dynamic characteristics of a bearing is a prerequisite for rotor dynamic design [5,6]. The dynamic coefficient of a bearing is typically used to describe the dynamic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The conducted research showed that the operating characteristics are highly dependent not only on the used material and bearings' geometry but also on the surface roughness of the mating parts. Sarrazin and Liebich [3] concentrated their study on conical foil bearings. Their work's novel findings show that the investigated bearings' proper functionality requires a non-uniform bearing clearance and identification of the critical axial force for operation stability.…”
mentioning
confidence: 99%